Penyelesaian Perkara Wanprestasi dalam Sistem Small Claim Court di Indonesia dan Malaysia - Rachmatullah, Denny; Setiawan, Ichwan (Postulat, 2026)
This study examines the effectiveness of Small Claim Court mechanisms under Supreme Court Regulation (PERMA) Number 4 of 2019 in Indonesia and Order 93 Rules of Court 2012 in Malaysia in resolving default disputes. Using a normative and comparative juridical approach, the research evaluates procedural speed, simplicity, cost efficiency, and substantive justice. The findings show that Indonesia applies a higher claim limit of IDR 500 million and utilizes electronic court systems that accelerate case resolution, but faces challenges related to digital infrastructure and uncertainty over judgment finality. Malaysia, by contrast, implements highly simplified procedures without mandatory legal representation and ensures strong enforcement mechanisms, yet is limited by a low claim ceiling of RM 5,000 and low public awareness. Overall, Indonesia excels in material scope and digitalization, while Malaysia demonstrates greater procedural efficiency and enforcement effectiveness. However, neither system fully achieves the principle of swift, simple, and low-cost justice. The study recommends strengthening digital infrastructure and legal certainty in Indonesia, and increasing claim limits and public outreach in Malaysia.